Методика определения электромагнитных параметров и плотности тока в обмотках роторов асинхронных двигателей - Вербовой, Андрей Петрович (НТУ "ХПИ", 2005)
Разработана методика определения электромагнитных параметров короткозамкнутой обмотки ротора асинхронного двигателя, которая отличается представлением короткозамкнутой обмотки ротора эквивалентной одновитковой обмоткой (w02 = 1, в литературе w02 = 0,5) с числом фаз, равным числу фаз обмотки статора (m02 = m01, в литературе m02 = Z2). Новая методика позволяет рассчитывать значения электромагнитных параметров и плотность тока с более высокой точностью.

This paper introduces a technique for determination of electromagnetic parameters of a squirrel-cage rotor winding in an induction motor. The technique treats a squirrel cage rotor winding as an equivalent single-turn winding (w02 = 1, in publications on the subject w02 = 0,5) with the number of phases equal to the number of the stator winding phases (m02 = m01, in publications m02 = Z2). The new technique makes it possible to calculate electromagnetic parameters and current density with higher accuracy.
A technique for determination of electromagnetic parameters and current density in rotor windings of induction motors
Keywords: короткозамкнутые обмотки; асинхронные двигатели; ферромагнитные роторы; плотность токов; электрические машины; induction motor; winding; electromagnetic parameters; phase